Mycobacterium abscessus and massiliense lung infection during macrolide treatment for bronchiolitis obliterans after allogeneic hematopoietic stem cell transplantation. Issue 1 (January 2018) - Miyake, Noriko; Chong, Yong; Nishida, Ruriko; Takenaka, Katsuto; Kato, Koji; Miyamoto, Toshihiro; Aono, Akio; Takaki, Akiko; Mitarai, Satoshi; Shimoda, Shinji; Shimono, Nobuyuki; Akashi, Koichi
Abstract: In patients undergoing allogeneic hematopoietic stem cell transplantation (allo-SCT), post-transplant lung infection is critical for their prognosis. Mycobacterium abscessus complex is not fully recognized as a nontuberculous mycobacteria (NTM) pathogen of post-SCT lung infection. Here, we present three post-allogeneic SCT patients who developed pulmonary infection caused by M. abscessus complex including M. abscessus and M. massiliense . In all three cases, macrolide antibiotics had been administered for bronchiolitis obliterans syndrome (BOS) before the confirmation of their infection, and macrolide resistance was noted in the M. abscessus isolates, one of which resulted in an unfavorable treatment outcome. It is important to consider M. abscessus lung infection as well as other NTM in patients receiving allo-SCT, particularly those receiving macrolide therapy for BOS.